1998
DOI: 10.1098/rspb.1998.0390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of warm sea–surface temperature anomalies on the blue petrel at the Kerguelen Islands

Abstract: Several long-term studies on Southern Ocean seabirds and seals have suggested a possible link between major declines in breeding performance and El Nin¬ o Southern Oscillation events. We report that the breeding performances and body condition of the blue petrel (Halobaena carulea) on the Kerguelen Islands is depressed by episodic, warm sea-surface temperatures (SSTs) in the winter before breeding. Lagged cross-correlations between SSTs in the Kerguelen sector and the Southern Oscillation Index indicate that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 28 publications
5
89
1
Order By: Relevance
“…The same is true for tropical modes of variability, e.g. Guinet et al (1998) found that warm SSTs are typically located south of the Kerguelen Islands within a year of, and between 4.2 and 5.4 years after, an El Niño event. How these anomalous SSTs influence the local climate of the islands is unknown.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The same is true for tropical modes of variability, e.g. Guinet et al (1998) found that warm SSTs are typically located south of the Kerguelen Islands within a year of, and between 4.2 and 5.4 years after, an El Niño event. How these anomalous SSTs influence the local climate of the islands is unknown.…”
Section: Introductionmentioning
confidence: 65%
“…It is important to note that Guinet et al (1998) only considered conventional El Niño events. Since the late 1970s, El Niño events have had a different structure with maximum SST anomalies in the central Pacific flanked by colder SSTs to the east and west ).…”
Section: Introductionmentioning
confidence: 99%
“…Physical environmental conditions controlling prey availability were the determining factors influencing breeding performance (Croxall et al 1988;Ainley and Boekelheide 1990;Jouventin and Weimerskirch 1991). Warm sea surface temperatures modifying zooplanktonic communities affected the breeding performance of blue petrels Halobaena carulea in the Kerguelen region (Guinet et al 1998). Similarly, the demonstrated effect of SIE variability on the growth of prey populations such as krill and salps (Smith a nd Nelson 1986;Loeb et al 1997) appeared to be central in explaining the linkages between sea-ice, food availability, and the breeding performance of top predators (Barbraud and Weimerskirch 2001;Bü ßer et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Seabird populations have been suggested as potential bioindicators of the variability of the Southern ocean marine ecosystem (Weimerskirch et al 2003;Guinet et al 1994Guinet et al , 1998Croxall 1992;Hunt et al 1992). Longterm data sets on variability in population size or reproductive performance of Antarctic seabirds are an invaluable tool to further assess this bioindicator role, especially with regard to sea-ice, a key-component of their ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Impacts of ENSO on reproduction of seabird populations have been detected in places far from the equatorial Pacific, where they often occur after a lag of few months or years (e.g., Ainley et al 1995;Guinet et al 1998;Chambers 2004;Quillfeldt et al 2007), depending on the distance of the site from the equatorial Pacific and on the time required for bottom-up processes to cascade to upper trophic levels (Monticelli et al 2007). The Southern Oscillation Index (SOI) summarizes the state of the ENSO on a global scale, and appears to be strongly related to the breeding success and survival of seabirds ranging widely, such as albatrosses and many petrels (e.g.…”
Section: South American Large Marine Ecosystems and Climatementioning
confidence: 99%